Peningkatan Kesejahteraan Masyarakat Melalui Budidaya Jangkrik Di Kota Tangerang Selatan - Sutariyono, Sutariyono; Saksana, Joned Ceilendra; Amalia, Fisy; Aisha, Neila; Adiguna, Patria; Nurrahman, Syafran; Herawati, Tuti; Tohiroh, Tohiroh; Saefullah, A (LPPM STIE Ganesha, 2024)
This activity aims to assess the benefits of cricket farming for improving community welfare in South Tangerang City. In economic and agroecological contexts, cricket farming offers an environmentally friendly solution for producing alternative food and feed. The method used in this study combines material presentations on cricket farming, direct observation, and practical discussions at the farming site. The program involves 30 farmers, workers, and local community members. The activity took place on Saturday, May 25, 2024, focusing on cricket farming management, including cage preparation, cricket maintenance until harvest, marketing, and financial management of the business. The results show that using technology in cricket farming not only increases productivity but also supports sustainability by reducing waste and optimizing resource use. Additionally, crickets have great potential as an alternative protein source that can support global food security. This study provides important insights into cricket farming, from cage preparation and maintenance to harvesting, marketing the products, and managing the business finances. The findings indicate that a more efficient and sustainable production system can enhance community welfare